Study of machine learning based recommendation techniques used by Ecommerce (International Journal of Engineering and Computer Science, 2017)
Customer who viewed this item wills also view that” is an intelligent as well as expert activity that keeps track of customers. Online shopping trends are based on the statistics which execute cross-selling mechanism. This intelligent algorithm will suggest your site visitors with products which were mostly explored by other customers on basis of maximum ratings, purchased or liked and viewed. These suggestions display on product pages that are based on the current product. Various Shopping application and web-sites are using different methods to attract customers. In this paper we are going to study the algorithm and introduction to machine learning approach to find how E-commerce uses recommendation techniques.